FAMILY AND YOUTH VULNERABILITY TO SUICIDAL BEHAVIOUR IN FIRST NATIONS: A COMPARISON OF RESERVE AND NON-RESERVE GROUPS - Michel Tousignant; Nathalie Morin; Livia Vitenti; Antoine Bibaud De Serres; Arlene Laliberté (International Journal of Child, Youth and Family Studies, 2014)
Family factors can influence vulnerability to suicide in the general population as well as among Aboriginal communities. This research compares First Nations families living in three contexts – on a reserve, in a small town, and in a metropolitan area – to verify if children on a reserve appear to have higher family vulnerability, as indicated by a measure of negligence/indifference. An interview was conducted with three non-random samples of Quebec First Nations parents. The first sample was selected from a reserve, the second from families living in small towns near a reserve, and the third from two metropolitan areas. The negligence score was based on the criteria of the Childhood Experience of Care and Abuse interview. Aboriginal families from the metropolitan areas obtained a lower rate of negligence than the reserve group, with an intermediate rate for the small town group. However, rates were high in all three settings. Informants from groups outside the reserve perceived the reserve as presenting more challenges to raising children than where they lived. Vulnerability of children is likely to remain high in this reserve in the near future. Initiatives that have the intention of empowering parents should be undertaken at the family level. Prevention should also focus on ecological factors such as housing, continuing education, and job creation, as well as family intervention.